2021
DOI: 10.3389/fcomm.2021.719652
|View full text |Cite
|
Sign up to set email alerts
|

A Test of Three Models of Character Reversal in Typically Developing Children’s Writing

Abstract: Multisensory learning to read involves, to a large extent, learning to write. A major problem in the initial teaching of handwriting is preventing children from producing reversed letters, especially when the reversed letters are identical to other letters. Torres et al. (2021) offer an efficient method for remediating this problem. Here, we analyze the reversals in their writing data, obtained on Brazilian first-graders (Mage = 6.0 years). Surprisingly, this analysis led to the observation that the first grad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 97 publications
0
1
0
Order By: Relevance
“…More specifically, Torres et al (2021), not referenced by Mather, showed that mirror writing invariance represents a major link to reading fluency acquisition in first graders [see also Fischer and Luxembourger's (2021) discussion of this research]. These researchers found that spending 7.5 hours in multisensory-motor training to distinguish mirrored letters, such as ''b'' versus ''d,'' together with post-training sleep, to increase learning consolidation, improved reading fluency, which became two-times faster than with traditional reading instruction.…”
Section: What Happens To the Relationship Between Writing And Reading...mentioning
confidence: 99%
“…More specifically, Torres et al (2021), not referenced by Mather, showed that mirror writing invariance represents a major link to reading fluency acquisition in first graders [see also Fischer and Luxembourger's (2021) discussion of this research]. These researchers found that spending 7.5 hours in multisensory-motor training to distinguish mirrored letters, such as ''b'' versus ''d,'' together with post-training sleep, to increase learning consolidation, improved reading fluency, which became two-times faster than with traditional reading instruction.…”
Section: What Happens To the Relationship Between Writing And Reading...mentioning
confidence: 99%